The Client’s Perspective on Forming a Counselling Alliance and Implications for Research on Counsellor Training - Bedi, Robinder P.; Davis, Michael D.; Arvay, Marla J. (Canadian Journal of Counselling and Psychotherapy, 2007)
The present study examined the client’s perspective on what helps form and strengthen the counselling alliance and aims to provide a preliminary catalogue of concrete client-identified alliance-building factors. Nine participants (four males, five females) currently or previously in counselling were interviewed using the Critical Incident Technique and asked to identify specific events and behaviours deemed most helpful to alliance formation. The nine participants provided 107 critical incidents, which were placed into eight mutually exclusive categories. These findings serve to inform the direction of future research and training aimed at developing counsellors’ alliance-formation competence.